Bobruisk line of defense at the end of June 1941 - S. E. Novikov; A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность", 2021)
This archaeographic publication is devoted to the study of the history of one of the many defensive battles that took place on the territory of Belarus at the end of June 1941. The article introduces into scientific circulation two documents previously unknown to researchers of the Soviet special services on the state of the 47th Rifle Corps. The commentary, based on the use of little-known documentary information, reveals the content of the traditional and new historiographic narratives about the defensive battles of the Red Army in the context of solving local problems of keeping one of the defensive lines on the Berezina River near the Belarusian city of Bobruisk by Soviet troops. The work is intended for specialists in the history of the Great Patriotic War